Tie my shoes Yes, I can - Golubeva, Evgenia (London YoYo books, 2022)
Laces, Loops and knots ! There is a lot to remember when tying your shoes, but practice makes perfect. Follow Ben as he learns to lace his sister's shoes and saves the day!
Scientific notions
Keywords: Science